Cereal-derived arabinoxylans: Structural features and structure–activity correlations. (February 2020) - Wang, Jing; Bai, Junying; Fan, Mingcong; Li, Tingting; Li, Yan; Qian, Haifeng; Wang, Li; Zhang, Hui; Qi, Xiguang; Rao, Zhiming
Abstract: Background: Arabinoxylans (AXs) are important constituents of hemicelluloses in the endosperm and outer layers of cereal grains, including corn, wheat, rye, barley, oat and rice. The enzymatic hydrolysis of AXs yields arabinoxylan-oligosaccharides. Recently, structure–activity correlations between AX fine structural features and antioxidative activities, prebiotic potentials and immunomodulatory properties have been introduced. Scope and approach: This review summarizes recent findings on the structural features of AXs from various cereal origins subjected to different extraction methods. The correlations between fine structural features (molecular mass, bound ferulic acid and arabinosyl substitutional positions) and the AXs' biological activities (antioxidative activities, prebiotic potentials and immunomodulatory properties) are introduced. The prospects for future research on these topics are also discussed. Key findings and conclusions: AXs exhibit very different characteristics, which are dependent on the cereal's origin and the extraction method. The three biological activities of AXs and arabinoxylan-oligosaccharides were closely correlated with their fine structural features. The bound ferulic acid mainly contributes to the antioxidant capacities of AXs. Arabinosyl substitutional position in the xylan backbone can target to alter the microbial population in the gut. The low molecular mass and arabinose substitution at the O-3 position mainly contribute to immunological properties. Highlights: The structure of arabinoxylans (AXs) from various cereals were summarized. The antioxidative, prebiotic, and immunomodulatory activities of AXs were detailed. The correlations between AXs' structure and biological activities were introduced. The enormous development potentials and prospects of AXs were discussed.